DETERMINANTS OF CAPITAL STRUCTURE: EMPIRICAL EVIDENCE FROM FRANCE - HUBY, P.A. (2017)
We investigated the influence and relationship of 7 determinants: Tangibility, NDTS, Profitability, ETR, Size, Growth and Risk, to the capital structure of 6707 French firms (whose 66% are small firms) for the period 2012-2016. Our results provide partial supports to both pecking order and tradeoff theory. Indeed, the tradeoff theory is endorsed by our finding that Tangibility of assets and Size are positively related to Leverage. The pecking order is supported by the fact that our most profitable firms leverage less than other companies. Our study has also revealed that notable differences exist across our 8 industry divisions but almost no evidence was found when focusing on the type of firms. Differences by divisions were found for ETR, Size and Growth. NDTS is never significant, and Risk is only significant and positively related to Leverage when regress by divisions. Overall our sign’s predictions were matched at 57% and 5 variables are significantly related to Leverage whether the emphasis is on Industry division or type of firms.